Efficiency of Hanguana malayana (Jack) Merr for Oil Adsorption - คิดดี พีรนาฏ; ด่านชัยประเสริฐ เอื้อการย์; ทองเนื้อแข็ง วิกาญดา; ชัยเจริญ ชามาดา (PSRU Journal of Science and Technology, 2018)
This research is a study of efficiency of Hanguana malayana (Jack) Merr. for oil adsorption. The objectives investigate the appropriate quantity and proper time of fiber and pretreatment fiber of Hanguana malayana (Jack) Merr. to adsorb oil and study the efficiency of fiber and pretreatment fiber of Hanguana malayana (Jack) Merr. to adsorb oil. The material adsorptions are fiber and pretreatment fiber of Hanguana malayana (Jack) Merr.. This study was used synthetic wastewater that was prepared by vegetable oil 10 ml mixed with water 500 ml. The treatment of oil adsorption was desired to use the quantities of fiber and pretreatment fiber of Hanguana malayana (Jack) Merr. at 1, 2, 3 and 4 g and adsorption time at 10, 20 and 30 min. The result showed that 4 g of both fiber and pretreatment fiber of Hanguana malayana (Jack) Merr. at 10 min for time adsorption are the best efficient of oil adsorption at 98.97 and 96.22 percent, respectively.